Evaluasi Kualitas Susu Sapi Perah Berdasarkan Manajeman Pemeliharaan Kandang - Sonya Putri Maharani; Okinara Risada (Fusion : Journal of Research in Engineering, Technology and Applied Sciences, 2025)
This study evaluated the quality of dairy cow milk through a literature review of husbandry management. Milk quality assessment includes physical, chemical, and microbiological aspects. Low milk quality is often influenced by poor housing management, feed contamination (e.g. Salmonella sp.), and unhygienic milking practices. This research method is a systematic literature review using databases such as Google Scholar, Scopus, and PubMed with keywords "dairy cow maintenance", "cow milk quality", "farm management", and "Salmonella contamination in milk". The results of the review indicate that milk quality is influenced by physical parameters (total solids, protein, fat, BPBL) and microbiological (TPC, JSS) which are closely related to sanitation and udder health. Crucial husbandry management factors include nutrition and feed, housing and environmental management, milking practices, udder health and mastitis prevention, and post-milking milk handling. To improve milk quality, the main recommendations include farmer education, implementation of Good Dairy Farming Practices (GDFP), animal health supervision, provision of cooling infrastructure, and incentive systems based on milk quality. Overall, comprehensive and sustainable maintenance management not only improves milk quality, but also the productivity and profitability of dairy farming businesses.